DETERMINATION OF HYDROXYZINE BY DIFFERENTIAL PULSE ANODIC VOLTAMMETRY USING CARBON PASTE ELECTRODE - Sayed I. M. Zayed; Amal A. H. Al-Talhi; Asmaa E. Al Thagafi (Journal of the Chilean Chemical Society, 2018)
The electrochemical oxidation of hydroxyzine dihydrochloride at carbon paste electrode has been studied in 0.04 M Britton-Robinson buffer pH 6.2 using cyclic and differential pulse voltammetry. The oxidation process has been shown to irreversible and diffusion controlled with adsorption characterstics. Based on these studies, simple, rapid, and sensitive differential pulse anodic voltammetric method has been developed for the determination of the drug over the concentration range 0.45-5.36 μg/ml, with detection and quantification limits of 0.27 and 0.90 μg/ml hydroxyzine dihydrochloride, respectively. The proposed method was successfully used for quantification of hydroxyzine dihydrochloride in Atarax tablets and spiked human urine.